Titulação da PEEP pela complacência e pressão de distensão de vias aéreas em pacientes sob anestesia geral - Nogueira, Beatriz Esteves (2019)
This work evaluated the influence of the resistive component on the determination of the positive end-expiratory pressure (PEEP) that minimizes the elastic work of the respiratory system in patients with healthy lung during cholecystectomy under general anesthesia. Twenty-five patients who underwent elective laparoscopic surgery received initial recruitment maneuvers and decreasing PEEP titration before and after pneumoperitoneum (PNP). The recruitment maneuver consisted of an increase of PEEP up to 20 cmH2O in controlled pressure mode, respiratory rate of 6 cycles/min and inspiration: expiration ratio of 1: 1. Afterwards, in Volume Controlled Mode, tidal volume (VT) of 6 mL/kg, PEEP was reduced from 20 to 6 cmH2O, with 2 cmH2O steps, 30s per step. At each step, the driving pressure (dP) was calculated from airway pressure using peak and plateau pressures. Additionally, the respiratory system (SR) static and dynamic compliances, and the estimated by the least squares method (Clsq) in a unicompartmental linear model were calculated at each step and the PEEPs corresponding to their maximum values were compared with PEEPs that minimized dP. Before PNP there were statistical differences only between the PEEPs obtained by dynamic dP and Clsq; after PNP, there were no differences between PEEPs. Considering the ease calculation of dynamic dP, without the need of pauses or the measurement of the VT, this method of measurement for individualizing PEEP in patients during general anesthesia is viable